The Effect of Thermal Treatment under Different Atmospheric Conditions on the Catalytic Performance of Nickel Supported on Porous Silica in the Gas-Phase Hydrogenation of Acetonitrile - Pilar Braos-García; Desireé Durán-Martín; Antonia Infantes-Molina; Dolores Eliche-Quesada; Enrique Rodríguez-Castellón; Antonio Jiménez-López (Adsorption Science & Technology)
A series of mesoporous silica-supported nickel catalysts (2.2 wt% Ni) were prepared by impregnation employing the incipient wetness technique using Ni(II) formate as the impregnation salt. Three different atmospheric conditions were employed during the thermal treatment: air, He and H 2 . The catalysts were characterised by chemical analysis, XRD, N 2 adsorption at −196°C, H 2 -TPR, H 2 -TPD and XPS. A direct relationship was found between catalytic activity in the gas-phase hydrogenation of acetonitrile and the Ni 2p 3/2 binding energy assigned to the Ni 0 atoms of the reduced catalysts, where the catalytic activity decreased with increasing binding energy. The best catalyst obtained was that prepared by thermal decomposition in air and subsequent reduction in a hydrogen atmosphere; this catalyst displayed a high metallic surface and a low value for the Ni 2p 3/2 binding energy of Ni 0 .